Integrative Skills Approach in Teaching English for Aircraft Maintenance Engineering - Nurul Jumiati; Muhammad Ariyudha Rio Satriabudhi (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2026)
Effective English and safe communication are crucial within the aviation industry. This study aims to explore English instructors’ perceptions and practices regarding the integrative skills approach in teaching English to Lion Group staff in the field of Aircraft Maintenance Engineering. Adopting a qualitative case study design, the research involved three instructors who were purposively selected for their reported implementation of the integrative skills approach in their teaching. Data were collected through interviews, classroom observations, and documentation, then analysed using thematic analysis. The findings reveal that the instructors hold positive perceptions of the integrative skills approach, believing that it effectively enhances learners’ English proficiency. They emphasised that the approach increases student engagement and motivation and provides a more holistic learning experience. However, the instructors also noted that its success largely depends on teachers’ preparedness and students’ readiness. In practice, they implemented structured pedagogical frameworks, such as the six-stage model (lead-in, meaning-focused input, language-focused learning, meaning-focused output, feedback and assessment, and follow-up activities), employed authentic materials, and incorporated reflective learning components. In conclusion, the integrative skills approach is perceived as an effective method for developing English proficiency and communicative competence in aviation contexts for Aircraft Maintenance Engineering.